Peningkatan Aktivitas Dan Kemampuan Berpikir Kritis Siswa Dalam Pembelajaran Matematika Melalui Model Pembelajaran Group Investigation Dengan Strategi PembelajaranInquiring Minds Want To Know (PTK Siswa Kelas VIII D SMP Al-Islam 1 Surakarta Tahun 2013/2014) - Calegiartanti, Rindang; , Rita P. Khotimah, S.Si., M.Sc (2014)
This research is conducted to improvement the activities and abilities of critical thinking by students using group investigation model with the inquiring minds want to know strategy. This research is a classroom action research (CAR). The receiver subject of action are the students of class VIII D SMP Al-Islam 1 Surakarta counted 36 students and the giver subject of action are mathematics teacher collaborated with the researcher. The method of collecting data was conducted by observation, documentation, and notes field sheet. The technical of analyzing data consists of: data reduction, data presentation, and conclusion drawing. The research result shows the improvement activities and students abilities of critical thinking through Group investigation model with inquiring minds want to know strategy. It can be seen by the percentage increasing of activity indicators, (1) doing exercise questions in front of class before the treatment 38,88% became 61,11%, (2) answering questions given by the teacher before the treatment 30,55% raised become 80,56%. While on indicators of critical thinking ability, that was (1) asking a various questions according to the learning concept before the treatment 8,33% became 63,88%, (2) proposing idea, opinion, and comments before the treatment 13,88% became 69,44%, (3) solving mathematics problem before the treatment 25% become 80,56%. From this research, can be concluded that application the Group investigation model with inquiring minds want to know strategy can improvement the activities and abilities of critical thinking by students in mathematics learning.